Studies on the Antimicrobial Activity and Brine Shrimp Toxicity of the Leaves Extract of Ageratum Conyzoides (Bangladesh Journal of Microbiology, 2016)
The purpose of this study is to evaluate the antimicrobial and cytotoxic properties of the leaves extracts of Ageratum conyzoides L. Ageratum conyzoides has been utilized for the treatment of various ailments. The crude methanolic extract of Ageratum conyzoides, n-hexane, chloroform and ethyl acetate soluble fractions of methanolic extracts were screened for their antimicrobial activity against a number of gram positive and gram negative bacteria by disk diffusion method. The crude extract and n-hexane soluble fraction of crude extract showed significant to moderate antimicrobial activity and chloroform, ethyl acetate soluble fraction of crude extract showed moderate to mild antibacterial activity against gram positive and gram negative bacteria. The zones of inhibition produced by the crude extract (methanolic extract), n-hexane, chloroform and ethyl acetate soluble fractions were found to be 14.89 mm - 19.40 mm, 14 mm - 19.40 mm, 10.66 mm - 13.50 mm and 9.50 mm - 13.26 mm respectively at a concentration of 30 mg/disc. Chloroform, n-hexane and ethyl acetate soluble fractions of methanolic extract of Ageratum conyzoides were screened for antitumor properties using brine shrimp lethality bioassay. A reputed cytotoxic agent vincristine sulphate was used as a positive control. From the results of the brine shrimp lethality bioassay it can be well predicted that nhexane, chloroform and ethyl acetate soluble fractions of methanolic extract of Ageratum conyzoides possess cytotoxic activity on shrimp nauplii. The median lethal concentration (LC50, the concentration at which 50% mortality of brine shrimp nauplii occurred) of n-hexane, chloroform and ethyl acetate were 245.42 mg/ml, 92.61 mg/ml and 6.35 mg/ml, respectively, comparison with positive control vincristine sulphate with 0.839 mg/ml.Bangladesh J Microbiol, Volume 29, Number 2, Dec 2012, pp 98-103